Further development of the strategy for European bison population in Belarus (European Bison Conservation Newsletter, 2016)
Discussed is the concept for the creation of European bison population in Belarus. Its main point is to connect three already existing large populations by creating three small satellite populations between them, in order to achieve a metapopulation that can be managed at country level. Presented are assumptions for the establishment of such satellite populations.
Keywords: European bison; Belarus; strategy; development; metapopulation